2019
DOI: 10.1186/s12966-019-0768-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of individuals with low versus high consumption of home-prepared food in a group with universally high dietary quality: a cross-sectional analysis of the UK National Diet & Nutrition Survey (2008–2016)

Abstract: BackgroundDespite inconclusive evidence, the idea that a lack of home food preparation and skills is a limiting factor in achieving a healthy diet is widespread. Cooking skills interventions proliferate, and several countries now mention cooking in their dietary guidelines. The aim of this study was to determine whether substantial consumption of home-prepared food is necessary for high dietary quality by exploring whether individuals can eat healthily while eating little home-prepared food. The diets of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Analyses of data from the National Health and Nutrition Examination Survey completed in the USA indicated that black respondents cooked at home less frequently than other groups [40]. However, further research from the USA [41] and UK [42] concluded that individuals that identified with an ethnic minority allocated more time to home food preparation and consumed more home cooked food than individuals that identified with an ethnic majority. Online food delivery service use could reduce home cooking, which might have implications for the overall diet quality of customers.…”
Section: Interpretation Of Findings and Further Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Analyses of data from the National Health and Nutrition Examination Survey completed in the USA indicated that black respondents cooked at home less frequently than other groups [40]. However, further research from the USA [41] and UK [42] concluded that individuals that identified with an ethnic minority allocated more time to home food preparation and consumed more home cooked food than individuals that identified with an ethnic majority. Online food delivery service use could reduce home cooking, which might have implications for the overall diet quality of customers.…”
Section: Interpretation Of Findings and Further Researchmentioning
confidence: 96%
“…Online food delivery service use could reduce home cooking, which might have implications for the overall diet quality of customers. Whilst it is possible to meet dietary guidelines through consumption of food prepared away-from-home, it may be more difficult and more expensive than through food prepared at home [42,43], and bound by the types of food outlet available [44].…”
Section: Interpretation Of Findings and Further Researchmentioning
confidence: 99%
“…As interventions to increase home food preparation encounter issues of cost and scalability, as well as showing equivocal evidence of long-term impact in participants [10–12], it is unclear that this justifies further policy action in terms of improving dietary quality. Our previous work suggests that it is possible to eat healthily while consuming very little HPF [32]; while an association with home food preparation exists, so may other behavioural routes to high dietary quality. In addition, the small contribution of HPF to the energetic intake of most participants suggests that changing home food preparation practices might have more limited potential to impact overall dietary quality than might be assumed.…”
Section: Discussionmentioning
confidence: 99%
“…As previously, food items listed in food diaries were classified by the authors as either requiring or not requiring home preparation [32]. All foods were classified as home-prepared except those listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Observational evidence suggests that higher frequency of making [1][2][3][4][5] and eating [4,6,7] home-prepared meals, while not a prerequisite for a healthy diet [8], is associated with improved dietary intake and health outcomes. Substantial energy has been devoted to understanding the modifiable determinants of home food preparation and increasing food preparation in households [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%